If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 2y) + (x + y) = 180 Remove parenthesis around (2x + 2y) 2x + 2y + (x + y) = 180 Remove parenthesis around (x + y) 2x + 2y + x + y = 180 Reorder the terms: 2x + x + 2y + y = 180 Combine like terms: 2x + x = 3x 3x + 2y + y = 180 Combine like terms: 2y + y = 3y 3x + 3y = 180 Solving 3x + 3y = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 3x + 3y + -3y = 180 + -3y Combine like terms: 3y + -3y = 0 3x + 0 = 180 + -3y 3x = 180 + -3y Divide each side by '3'. x = 60 + -1y Simplifying x = 60 + -1y
| 7x^2-12x-27=0 | | 1.5lnx=0 | | 23m-8-2m-6= | | 3+3n-1=6n+2-2n | | 5(x-1)-3(x-2)=2 | | 55-5x=80-5x | | -3.5-1.25r=-13.5 | | x-6*(-1)=3 | | -3.5-1.25r=13.2 | | ln(2+x)=0 | | -3(3y+5)-5=-6(y+5)+3y | | 6x-3y=27 | | 1.5lnx-2.5lnx=0 | | 5x/7+1/14=7/28 | | 35+17x= | | 0-6y=3 | | (y+.4)(y+.4)=.84 | | 12x+2x+4c= | | (x-1/3)^2+(x-1/3)(x+2/9)=0 | | 3x^2-12x-56=0 | | -4x+3y=-3 | | 4(2q+10)=4q-12 | | 7(k-3)=-4(-1-6k) | | 13x+20=3x+30 | | 5Y^2+12Y=8Y-5 | | -2x+12y=-30 | | 25n+16n= | | -163+10x=8x+17 | | 5x-4y=38 | | 3x+16=10x+54 | | 13+8=-3(5x-7) | | 15-5/2=9+1/2x |